Hydrodynamic Regimes, Knudsen Layer, Numerical Schemes: Definition of Boundary Fluxes (Advances in Applied Mathematics and Mechanics, 2011)
We propose a numerical solution to incorporate in the simulation of a system of conservation lawsboundary conditions that come from a microscopic modeling in the small mean free path regime. The typical example we discuss is the derivation of the Euler system from the BGK equation.The boundary condition relies on the analysis of boundarylayers formation that accounts from the fact that the incoming kinetic fluxmight be far from the thermodynamic equilibrium.